Thou Shalt Not Breach : The Impact on Sovereign Spreads of Noncomplying with the EU Fiscal Rules - Diaz Kalan, Federico (IMF Working Papers; Working Paper ;, 2018)
There is evidence that fiscal rules, in particular well-designed rules, are associated with lower sovereign spreads. However, the impact of noncompliance with fiscal rules on spreads has not been examined in the literature. This paper estimates the effect of the Excessive Deficit Procedure (EDP) on sovereign spreads of European Union member states. Based on a sample including the 28 European Union countries over the period 1999 to 2016, sovereign spreads of countries placed under an EDP are found to be on average higher compared to countries that are not under an EDP. The interpretation of this result is not straight-forward as different channels may be at play, in particular those related with the credibility and the design of the EU fiscal framework. The specification accounts for typical macroeconomic, fiscal, and financial determinants of sovereign spreads, the System Generalized Method of Moments estimator is used to control for endogeneity, and results are robust to a range of checks on variables and estimators.